Development and characterization of sugar palm [Arenga pinnata (Wurmb.) Merr]/glass fiber reinforced poly (lactic acid) hybrid composites for motorcycle components - Khan, Sherwani Shah Faisal (2021)
The automotive industry is always focusing on advanced composites to improve the strength-to-weight ratio. To meet this need, many unique composite materials have been developed or fabricated in the automotive industry. Both synthetic and natural polymers are being used in the production of composite materials for automotive applications. The use of synthetic polymers derived from petroleum sources is hazardous to the environment. The majority of the motorcycle's body frame parts are composed of an ABS (Acrylonitrile Butadiene Styrene) engineering thermoplastic. ABS is a petroleum-based plastic that is non-biodegradable, is not a renewable resource, and is not environmental friendly. Because of the environmentally hazardous properties of ABS plastic, researchers are leaning toward biodegradable plastic in order to save the environment. This might have been achieved with biodegradable materials such as poly(lactic acid) (PLA) and natural fiber composites. PLA is an excellent choice for replacing ABS since it is a bio-degradable type of plastic that is made from plant-based materials such as corn starch or sugarcane. PLA is a biobased, biodegradable, biocompatible, compostable, and non-toxic polymer with low material and manufacturing costs as well as desired mechanical properties. Sugar palm [Arenga pinnata (Wurmb.) Merr] fiber has been chosen to mixed with PLA and glass fiber, because of its availability, particularly in Southeast Asia, and its proven performance. Therefore, this research describes the development and characterization of hybrid and non-hybrid composites of sugar palm and glass fiber reinforced poly(lactic acid) for Modenas Kriss 110 motorcycle battery housing part. To evaluate the impact of different wt.% of fiber loading, treatment and hybridization, hybrid and non-hybrid sugar palm/glass fiber (SPF/GF) reinforced PLA composites were developed using a Brabender Plastograph, followed by a compression molding method. Initially the effect of various fiber loading i.e. 10 wt.%, 20 wt.%, 30 wt.% and 40 wt.% on poly(lactic acid) were determined. The best physical, tensile, and flexural properties for SPF/PLA composites were exhibited by 30 wt.% SPF loading, whereas the maximum impact strength value was shown by 40 wt.% SPF loading. The major difficulty associated with natural fiber is its hydrophilic nature and lack of adhesion with the hydrophobic matrix. The inherent difficulties can be solved by chemical treatments and hybridization. In this work, the sugar palm fiber was treated with alkaline (NaOH) and benzoyl chloride (C6H5COCl) solutions. Various methods were used to evaluate the physical and mechanical properties of treated and untreated sugar palm fiber/PLA composites. The treated SPF improved in physical (density, thickness, swelling, and water absorption), mechanical (tensile, flexural, and impact) as well as morphological properties of SPF/PLA composite and became more hydrophobic, when compared to the untreated fiber SPF/PLA composite. Among the two treatments, alkaline treatment improved tensile, flexural, and impact strength, (17.08 MPa, 32.34 MPa, and 4.39 kJ/m2) whereas a benzoyl chloride (BC) treatment improved tensile and flexural modulus (602 MPa and 1916 MPa) while also increasing hydrophobicity, and for untreated SPF/PLA composite the tensile, flexural, impact strength, tensile, and flexural modulus were 6.85 MPa, 6 MPa, 1.56 kJ/m2, 500 MPa, and 850 MPa. Morphological, FTIR, and flammability investigations confirmed that the 6% alkaline SPF treatment improved the physical, tensile, flexural, and impact properties of SPF/PLA composites. In general, the alkaline treatment (6% NaOH conc.) performed better than the BC treatment. The analysis of a hybrid and a non-hybrid composite of SPF/GF reinforced PLA composite revealed a promising improvement in the composite's physical, mechanical, and morphological properties. The alkaline treatment improved the tensile strength, modulus, flexural, and impact strength by 19%, 3%, 17%, and 15% for SPF/GF/PLA hybrid composite, while the BC treatment improve the tensile modulus and impact strength by 19% and 3%. In the last section of this study, the mechanical properties of SPF/GF/PLA hybrid composites such as creep, compression, and hardness were determined in comparison to commercially available ABS plastic motorcycle battery housing parts. Furthermore, the results revealed that hybridization of treated SPF with GF improved the overall performance of the composite as compared to both untreated or SPF/PLA single system composite. In conclusion, when compared to ABS plastic, employing treated SPF/GF/PLA hybrid composite results in a high-strength biodegradable plastic suitable for Modenas Kriss 110 motorcycle battery housing parts.